PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PREDIKTABILITAS LABA PADA PERUSAHAAN MANUFAKTUR DI SEKTOR ANEKA INDUSTRI DI INDONESIA - Lilyani Kartika Sinatra; Juniarti Juniarti (Business Accounting Review, 2016)
This study aimed to investigate the influence of Corporate Social Responsibility to the predictability of the company's profit. Corporate Social Responsibility variables measured by using the Global Reporting Initiative (GRI) Index 3.1. Variable earnings quality measured by using earnings predictability. The control variables in this study were firm size and leverage. This research was conducted at the company go public in Various Industries sector listed in Indonesia Stock Exchange and has annual report on the period of 2010-2014 with a sample of 120 observations. The results showed that the Corporate Social Responsibility positively related to the predictability of earnings, while firm size negatively related to the predictability of earnings and leverage positively related to earnings predictability.